Socio-demographic determinants of electricity consumption across vietnamese households - Duc Hong Vo (PLoS ONE, 2025)
Reducing household energy consumption is generally considered a key force in limiting the adverse effects of human beings on climate change. As such, understanding the socio-demographic determinants of household electricity consumption across Vietnamese households plays an important role. However, this understanding has largely been neglected in the existing literature, particularly for Vietnam. This study focuses on understanding the role of socio-demographic factors electricity consumption across Vietnamese households using two waves of the Vietnamese Household Living Standards Surveys (VHLSS) in 2012 and 2020. The three-stage least squares estimation has been used to address the endogeneity problem and examines the reverse causality between income and electricity consumption of the households. The results show that household income and the educational level of the household head are the two factors with the most significant impacts on household electricity consumption. Electricity consumption expenditure also significantly and positively impacts household income. The economies of scale are confirmed between the number of household members and electricity consumption, meaning that larger families consume more electricity. In addition, our findings show that the differences in electricity consumption between the richest and poorest household groups increased sharply in 2020. These key findings call for policies to support disadvantaged households in Vietnam and that the current structure of the electricity tariff has failed to capture the disproportional level of electricity consumption between the richest and poorest groups of Vietnamese households.